2005
DOI: 10.1111/j.1464-5491.2005.01412.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection‐related Type 1 diabetes mellitus

Abstract: The simultaneous development of HCV infection and diabetes-related autoantibodies suggest a relationship between HCV and Type 1 DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 35 publications
0
20
0
1
Order By: Relevance
“…According to a report by Mehta et al, the incidence of type 2 diabetes mellitus is about three times higher in HCV-infected individuals than in noninfected individuals overthe age of 40 years 6. In contrast it has also been reported that the incidence of type 1 diabetes mellitus as a complication is lower than that of type 2 diabetes mellitus 7. It has also been reported that the pancreas-associated autoantibody (including antiglutamic acid decarboxylase antibody) positivity rate in HCV patients is 3% before the start of IFN therapy but increases to 7% thereafter 1.…”
Section: Discussionmentioning
confidence: 98%
“…According to a report by Mehta et al, the incidence of type 2 diabetes mellitus is about three times higher in HCV-infected individuals than in noninfected individuals overthe age of 40 years 6. In contrast it has also been reported that the incidence of type 1 diabetes mellitus as a complication is lower than that of type 2 diabetes mellitus 7. It has also been reported that the pancreas-associated autoantibody (including antiglutamic acid decarboxylase antibody) positivity rate in HCV patients is 3% before the start of IFN therapy but increases to 7% thereafter 1.…”
Section: Discussionmentioning
confidence: 98%
“…Gastrointestinal infections and in more extreme cases myocarditis (inflammation of the heart) and pericarditis (inflammation of the sack surrounding the heart) T1D [92][93][94][95] Hepatitis B Hepadnaviridae Liver inflammation SLE [96,97] Hepatitis C Hepadnaviridae Liver inflammation MG [98,99], GD [100,101], T1D [102,103], SLE [104]…”
Section: Coxsachie B Virus Picornaviridaementioning
confidence: 99%
“…Even rarer are reports on the potential association between autoimmune diabetes and acute HCV infection. Only two cases have been described in the literature [151,152] . Several mechanisms have been postulated to initiate the process.…”
Section: Hcv-infected Patients With T1dmmentioning
confidence: 99%